The relationship between media and public health in the CIS countries: How information channels influence the development of healthy behaviors - Yevgeniy Akchurin (Scientific Research and Experimental Development, 2024)
This article focuses on how the media impacts the setup of information channels to promote healthy lifestyles among citizens. Mass media play a crucial role in the media environment, serving to unite local communities and enhance the economic and socio-cultural development of the population.